Role of transporters in the mechanism of paraquat resistance of horseweed (Conyza canadensis (L.) Cronq.) - Soós, Vilmos (Acta Biologica Szegediensis, 2005)
In paraquat resistant biotype of C. canadensis inducible proteins are supposed to play a role in the mechanism of resistance. Here we studied the uptake and intracellular localization of Pq, the effect of selective inhibitors on the uptake and sequestration, and the Pq induced changes of gene expression in susceptible and resistant biotypes. In resistant plants Pq was found to reach the chloroplast in a short time, however, to the end of recovery period it was removed to vacuoles and stored for one month. Sequestration to vacuoles was inhibited by nitrate. Pq upregulated numerous genes in susceptible and resistant biotypes. Sequencing made the opportunity to identify 4 genes; the iron storage protein Ferritin2, a Myb transcription factor, CAT4 amino acid transporter and a xenobiotic transporter. Transporters expressed at higher levels in resistant plants as compared to susceptible ones. They are supposed to play important part in paraquat resistance.